Fragments - Wells, Dan, 1977- (New York : Balzer + Bray, 2013)
"With the Help of Samm and Heron, Kira sets out on a desperate search for clues as to who she is, while Marcus and the remaining human population gear up for war with the Paritals"--
Keywords: Identity -- Fiction; Medical care -- Fiction; Survival -- Fiction; Robots -- Fiction; Science fiction